Damage evolution of RC beams under simultaneous reinforcement corrosion and sustained load - Shen, Jiansheng; Gao, Xi; Li, Bo; Du, Kun; Jin, Ruoyu; Chen, Wei; Xu, Yidong (MDPI AG, 2019)
To accurately obtain the performance of concrete structures in coastal regions, it is necessary to correctly understand the damage evolution law of reinforced concrete (RC) members under real working conditions. In this paper, four RC beams, subjected to different levels of corrosion and sustained load, are first tested. Reinforcement corrosion coupled with sustained load increases the number and width of cracks at the soffit of beams but decreases their loading capacities. Crack width of the corroded beam under 50% of designed load is two times of that under 30% of designed load. Residual loading capacities of the corroded beams subjected to 30% and 50% of designed load are 87.5% and 81.8% of the control beam. A finite element model is developed for the corroded RC beams. Due to less confinement, concrete below and at the sides of reinforcements is subjected to a higher stress, compared to concrete above the reinforcements. Corrosion expansion of reinforcements is successfully modelled by a temperature-filed method, as it properly simulates the damage evolution of the corroded RC beams. As a result, concrete cracking, caused by the reinforcement corrosion, is well captured. Coupling reinforcement corrosion with sustained load significantly increases the damage level in RC beams, particularly for those subjected to a high sustained load. The whole damage evolution process of concrete cracking due to corrosion expansion under the coupling effect of sustained loading and environment can be simulated, thus providing a reference for the durability evaluation, life prediction, and numerical simulation of concrete structure